GROWTH, YIELD, AND ANTIOXIDANT TRAITS OF DIFFERENT PARTS OF BEETROOT AS AFFECTED BY VERMICOMPOST AND GLUTATHIONE - Al-Khafaji, Aseel M.H. H.; Al-Amri, N. J. K.; Al-Dulaimi , N. H. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to assess the impact of vermicompost, glutathione, and their interaction on beetroot (Beta vulgaris L.) growth, yield, and antioxidant traits. The experiment carried out at vegetable field of the College of Agricultural Engineering Sciences - University of Baghdad during fall season 2019. The experiment was conducted using factorial arrangement within Randomized Complete Block Design with two factors and three replicates (3X3X3). Applying vermicompost before cultivation represented the first factor (0, 15, 30 ton.ha-1), which symbolized (V0, V1, V2). Glutathione (0, 75, 150 mg.L-1) which symbolized (G0, G1, G2) represented the second factor. Results showed the superiority of secondary interaction treatment V2G2 in producing significant increases in dry weight of vegetative growth (50 g.) chlorophyll concentration in leaves (244.6mg.100-1g FW), Betacyanins in leaves and tuber roots (52.67, 89.33 mg.100ml-1) respectively scavenging activity for DPPH in leaves and root tubers (97.33, 91.66 %) respectively, and tuber root weight (200 g).